2007
DOI: 10.1097/mpg.0b013e31802c41f3
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of Tumor Necrosis Factor‐α but Not MDR1 Influence Response to Medical Therapy in Pediatric‐Onset Inflammatory Bowel Disease

Abstract: In our pediatric cohort, the promoter -308A polymorphism of TNF-alpha but not the MDR1 gene is significantly involved in the predisposition to both CD and UC. This polymorphism carries a significant reduction in response to steroid therapy, probably leading to a more frequent need for surgical resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 72 publications
3
51
0
2
Order By: Relevance
“…Baldassano et al 17 recently described a small cohort of 142 children with CD: 86% had involvement of the small bowel and colon (Ϯ upper GI tract). Cucchiara et al 18 showed in an Italian cohort of pediatric CD patients with Ն1 year of follow-up (n ϭ 200) that 58% had ileocolonic CD (using the Vienna classification). 18 Our data in UC are also consistent with the hypothesis that childhood-onset disease has a very high bias toward extensive disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baldassano et al 17 recently described a small cohort of 142 children with CD: 86% had involvement of the small bowel and colon (Ϯ upper GI tract). Cucchiara et al 18 showed in an Italian cohort of pediatric CD patients with Ն1 year of follow-up (n ϭ 200) that 58% had ileocolonic CD (using the Vienna classification). 18 Our data in UC are also consistent with the hypothesis that childhood-onset disease has a very high bias toward extensive disease.…”
Section: Discussionmentioning
confidence: 99%
“…Cucchiara et al 18 showed in an Italian cohort of pediatric CD patients with Ն1 year of follow-up (n ϭ 200) that 58% had ileocolonic CD (using the Vienna classification). 18 Our data in UC are also consistent with the hypothesis that childhood-onset disease has a very high bias toward extensive disease. This observation is also consistent with other datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have also tried to identify genetic factors associated with response to treatment. Polymorphisms in multi-drug resistant 1 (MDR1), TNF and migration inhibitory factor genes have been associated with corticosteroid refractoriness or sensitivity in CD and UC [45][46][47] . MDR1 polymorphism has also been associated with a higher risk of cyclosporine failure in patients with steroid-resistant UC [48] .…”
Section: Genetic Predictors Of CD Coursementioning
confidence: 99%
“…However, whether this variant is itself functional or in LD with the actual causative allele is still unclear (41,42). In addition, with the exception of our pilot study in children with IBD [40] no evidence of correlation of TNF-α polymorphism with response to medical therapy has been demonstrated.…”
Section: Discussionmentioning
confidence: 50%